The Status of Video Games as Self-Involving Interactive Fictions: Fuzzy Intervals and Hard Identifications - Kristina Šekrst ([sic], 2023)
The goal of this paper is to see how mental and language representations are unique from a video-game perspective, using two main criteria. First, I will posit that the level of being both an interactive work of fiction and a self-involving interactive fiction belongs to a fuzzy interval and that some works – and, therefore, some video games – are more immersive than others. Second, I will observe how propositions tie the player’s representations of the real world and the game world. Starting from psychological theories of pretense in children’s make-believe games, I will then expand Nichols and Stich’s cognitive theory of pretense to include an extra layer related to the game world, i.e., player-specific representations that govern player-specific propositions. The representations dealing with the work world are the socially shared ones, while the possible-world representations, dealing with most of the game world, are player-specific and tied to unique language use.Keywords: self-involving interactive fiction, cognitive theory of pretense, game world, pretend play, video game representations